Dynamic Stray Current Measuring Methods in Urban Areas - Katarina Vranešić; Marijana Serdar; Stjepan Lakušić; Václav Kolář; Andrea Mariscotti (The Baltic Journal of Road and Bridge Engineering)
In areas where urban tracks are used as public transportation, dynamic stray currents cause high maintenance costs for the tracks and metal structures near the tracks. S tray currents caused by rail vehicles depend on many factors (traffic density, vehicle speed, acceleration and deceleration, soil and track moisture), so it is very difficult to get a clear picture of the harmfulness of the stray current based on the results of a single field measurement. However, there are several measurement methods that can be used to determine the presence of stray currents and predict appropriate track maintenance actions. Some of these methods are described in this article, namely the use of stray current mapper, measurement of rail potential and rail current, measurement at the stray current collection system, and the use of non-destructive sensors. In track construction, measuring the electrical potential between rail and ground is one of the most common methods of detecting the damaging influence of stray current.